Eucalyptus extraction with grapple skidder: Operational productivity approach and production costs - Miyajima, Ricardo Hideaki [UNESP]; De Souza Passos, José Raimundo [UNESP]; Fenner, Paulo Torres [UNESP]; Simões, Danilo [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2020)
Among the activities of the mechanized forest harvesting, one of the most important is the extraction of eucalyptus trees, commonly carried out by means of the grapple skidder which is an intrinsic machine for harvesting modalities, currently used in Brazil. Therefore, the time and method study technique was applied to determine the production costs of operating a grapple skidder under different operating conditions. The study was conducted in the central western region of São Paulo State, where there was a forest planted with Eucalyptus platyphylla. The tree extraction was carried out by a John Deere grapple skidder. The time and study method was applied to determine the productivity per effective hour of the self-propelled machine, in addition, the methodology by the Food and Agriculture Organization of the United Nations (FAO, 1992) was adopted to estimate the programmed hourly cost of the self-propelled machine. The production cost of the operation was obtained by the ratio between the programmed hourly cost of the machine and the effective productivity. The analysis of the results showed that the times of the operating cycle elements with grapple skidder displacements are those that have greater representativeness in the total operation time, and that the productivity per effective hour of the self-propelled machine with grapple skidder is influenced by the extraction distance and by the slope of the terrain.
Extração de eucalipto com grapple skidder: Abordagem de produtividade operacional e custos de produção
Keywords: Decision support; Eucalyptus; Planted forest; Time and method; Wood harvesting